Comparative studies of the biodiesel fuel jet development dynamics in common rail and conventional design fuel systems - Kulmanakov, Sergey P.; Lebedevas, Sergejus; Kulmanakov, Sergey S.; Lazareva, Nadežda; Rapalis, Paulius (Transport, 2019)
The results of comparative diesel and biodiesel (Rapeseed oil Methyl Ester (RME) and Rapeseed Oil (RO)) fuel jet structure studies by optical scanning method are presented. There is an interrelation between the dynamics of fuel jet development by the Common Rail (CR) with single-phase injection and Conventional Design System (CDS) and the parameters of mixture formation, which are typical for transferring the operation of the Diesel Engine (DE) from mineral diesel to RME and RO. The structure of the Diesel Fuel (DF) jet is significantly more heterogeneous by the size and number of droplets in CDS in comparison with CR. From the moment of the injection the presence of zones less saturated with fuel contributes to a relatively short induction period – 5° ca. compared to 11…12° ca. in the CR system. Using RME in the CR system in comparison with DF, increases the heterogeneity of the fuel jet, thereby causing a shorter (by 1…2° ca.) induction period in the whole investigated range of injection pressures of 60…160 MPa. The injection of a non-heated RO is accompanied by the shape and structure fluctuations of the fuel jet. RO heating to 65 °C stabilizes the structure of the jet and increases the share of less saturated zones. Promising way of use for the optical scanning method in the mathematical modelling of the DE working process is proposed.